Menelaah Rencana Kenaikan Tarif PPN Berdasarkan Bukti Empiris Serta Dampaknya Secara Makro Ekonomi - Nur Farida Liyana (JURNAL PAJAK INDONESIA, 2021)
The plan to increase the VAT rate to 11 percent by 2022 has caused anxiety in the community. In the midst of the COVID-19 pandemic and the economy has not yet recovered, the idea of ​​rising commodity prices which is then accompanied by inflation is certainly disturbing not only for entrepreneurs but also for ordinary people. For this reason, in this paper, we carry out empirical evidence regarding the relationship between VAT and economic growth and the national saving rate in Indonesia. Then we will see the impact of the planned increase in the VAT rate on a macroeconomic basis by comparing the experience of Japan which has increased its VAT rate by 3 (three) ) times over the last 15 years. It was concluded that what the government was doing was on the right track because empirical evidence by performing OLS regression said that there was a significant positive relationship between VAT and GDP and national saving. So that what the government is doing is on the right track, raising the VAT rate is expected to encourage economic growth and attract foreign financing to Indonesia. However, it is necessary to first analyze the impact of the increase in the VAT rate on the macro economy. Based on lessons learned from Japan, it turns out that the increase in the VAT rate is not able to increase consumption and economic growth, but instead raises inflation. This needs special attention for the Government of Indonesia so that efforts are needed to mitigate these things.